Stimulus spatial properties and duration of adaptation influence on colour perception constancy - Daugirdienė, Aušra; Vaitkevičius, Henrikas (Psichologija, 2001)
The effects of adaptation duration on colour constancy were studied under two test illuminants (s and A) and two types experimental conditions using neutral (N7) Munsell chips and asymmetric colour matching. The influence of adaptation duration was quantified by calculating colour difference EL,a,b between the chromaticities for the perceived neutral Munsell chip’s colour after adaptation to the test illumination and against the standard (C) illuminant. The EL,a,bmeasure was used because the intention of this study was to measure changes in colour-perception, during different adaptation duration. Adaptation was only observed in experiments with uniform adaptation field, but not in a spatially complex background with introduced blank surround. We could say, that colour of test chip is determinated by difference in colour of test chips and background, and colour of background. In turn the colour of background is also determined by difference in colour between background and blank surround. Since there is no adaptation in blank surround, noting changes. Thus there is no influence of observation time on perceived colour. Then the adaptation field is uniform, we conclude from results the presence of two components of chromatic adaptation, that differ with respect to their time - constants and stimulus spatial properties. A fast component with a time of approximately 5 s, witch does respond to contrast, and a second, relatively slow process, witch has a time of 60 s and depends on stimulus spatial properties.